NEW FUNCTION
Function Expression :
\[f(x)=\frac{(2x^2+7x-7
)}{(2x-2
)} \]
Domain
\[\left]-\infty, 1\right[ \cup \left]1, \infty\right[ \]
Limits
\[\lim_{x \rightarrow-\infty}f(x) = -\infty \]
\[\lim_{x \overset{<}{\rightarrow1} }f(x) = -\infty \]
\[\lim_{x \overset{>}{\rightarrow1} }f(x) = +\infty \]
\[\lim_{x \rightarrow+\infty}f(x) = +\infty \]
\[ \]
Derivate
\[f^{\,\prime}(x)=\frac{4 x + 7}{2 x - 2} - \frac{2 \cdot \left(2 x^{2} + 7 x - 7\right)}{\left(2 x - 2\right)^{2}} \]
\[f^{\,\prime}(x)=\frac{x \left(x - 2\right)}{x^{2} - 2 x + 1} \]
\[ \]
Integral
\[F(x) = \frac{x^{2}}{2} + \frac{9 x}{2} + \log{\left(x - 1 \right)} \]
Sign Table
Variation Table
Plot
Elapsed Time: 0.0249 seconds